Memperkokoh Ideologi Pancasila - Hendri, Hendri (Universitas Pendidikan Ganesha, 2024)
A national consensus affirms Pancasila as Indonesia’s state foundation and national ideology; the challenge for the next generation particularly santri is to internalize its principles and translate them into sustained practice. This study describes and analyzes how pesantren strengthen santri’s Pancasila ideology. Using a qualitative approach, data were collected through observation, semi-structured interviews, and document analysis, and were examined with thematic analysis. Findings indicate three mutually reinforcing domains of formation: (1) role modeling through the exemplarity of kyai/ustaz, disciplined routines, deliberation (musyawarah), and everyday adab; (2) education via explicit integration of Pancasila values into religious and civics instruction, enrichment of national literacy, and reflective assignments; and (3) pesantren activities [i]including habituation of worship and moral conduct, student organizations, community service, and ceremonial events that cultivate mutual cooperation (gotong royong), tolerance, and rule observance. Taken together, a pesantren ecosystem that combines exemplar, curriculum, and authentic practice effectively strengthens santri’s understanding, attitudes, and enactment of Pancasila values. Practical implications include capacity building for educators in values-based pedagogy, development of reliable affective–behavioral assessment tools, stronger pesantren–government–community partnerships, and adaptation of teaching materials to address digital-era challenges and risks of intolerance. Future research should broaden institutional coverage and employ mixed-methods designs to estimate long-term impacts on character formation and civic participatio